Fostering Gender Equality and Equity in Local Governance: A Comparative Study of the Experiences in the Philippines and Pakistan - Sarmiento, La Rainne Abad (Review of Women's Studies; Vol 13 No 2 (2003): Review of Women's Studies Volume XIII, Number 2 (July-December 2003), 2004)
---